Development of target localization and tracking for vtol (vertical take off and landing) uavs - Wu, Yuze. (2012)
Unmanned Aerial Vehicles (UAVs) are self-piloted aircrafts that can carry cameras, sensors, communications equipment or other payloads. Now the UAV becomes significantly important in military and civilian domain and normally preferred for mission that is dangerous and impossible for manned aircraft.